An in vitro scanning electron microscope study to evaluate the efficacy of various root conditioning agents - Jaishree Garg; Rajkumar Maurya; Ankur Gupta; Pradeep Tandon; Krishna Kumar Gupta; Amitabh Srivastava (Wolters Kluwer Medknow Publications, 2015)
Aim: The purpose of present study was to investigate the scanning electron microscopic alterations produced on scaled and root planed dentin surfaces after application of different etching modalities namely citric acid, tetracycline hydrochloride and ethylenediaminetetraacetic acid (EDTA). Materials and Methods: Eighty specimens of teeth were collected and categorized into four groups. In group 1, control group specimens were treated with normal saline for 3 min, group 2 specimens were treated with citric acid, group 3 specimens were treated with tetracycline hydrochloride for 3 min and group 4 specimens were treated with 15% EDTA. Results: Opening of dentinal tubules was seen in all specimens except for control group that was treated with normal saline. The total number of tubules seen was highest in citric acid group as compared to tetracycline hydrochloride and EDTA Group. The total number of patent tubule opening was highest in citric acid as compared to EDTA and tetracycline. The diameter of patent dentinal tubules in citric acid group was more than EDTA and tetracycline. Conclusion: The study showed that all the three agents were effective in removing the smear layer however number of patent and wider diameter dentinal tubules was seen in vitro best in citric acid than EDTA and then in tetracycline hydrochloride. Hence, citric acid group is more efficient than EDTA and tetracycline HCl group in removing the smear layer and in opening of number of patent dentinal tubules.